Subtitle, video marked and audio description at the spanish current television - Álvarez Álvarez, Mª de las Nieves (Historia y Comunicación Social, 2014)
The Broadcasting Act 2010, and subsequent amendments, was designed to facilitate disabled the access to the national audiovisual landscape. Through clearly defined quotas, Spanish mass media are required -among others- to subtitle for people with hearing problems, Video Marked for people with severe hearing impairments and audio description for the blind. To this end, the research shows an X-ray on the passage of legislative theory to actual practice with incidence of the following discrepancies: 1. Subtitled. Not always carried out in the case of environmental indications, limiting the work to mere text subtitles. 2. Video marked. Deaf Associations prefer the translator’s image superimposed on the left of the screen image, detail that goes unnoticed on a recurring basis. Moreover, in some cases, the programs offering this service are not varied and there are several passages to the same product to cover the required quota. On the other hand, the broadcast hours are late at night or at dawn. 3. Audio Description. The audio tracks 1 and 2 are ordinarily kept for the channel itself audio, being tracks 3 and 4 those used for the dual system, ie, for the program audio together with audio description system. Doing so implies that the television channels lose the ability to broadcast original version since they are using those tracks for audio description, that’s why there is the possibility of adding a 5th audio track only for audio description (on broadcast file, on tape it only has four channels). The latter problem is based on the fact that not everyone at home can select the 5th audio (which in TV audio means a 3rd audio option: the standard, the dual and an additional one).
Keywords: Spain; Broadcast Act; Audiovisual Law 2010; subtitle; video marked; audio description.